Effect of Flash Card Media Effectiveness on Beginning Reading Ability and Symbolic Thinking in Early Childhood 5-6 Years: Case Study in Kindergarten. Imam Syafi'I Jember Odd Semester 2022-2023 Academic Yea - Lely Widorini Kurniawati (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2023)
Learning media is an important tool in supporting the effectiveness of learning in schools, one of the visual learning media uses flash card media that displays a series of cards containing pictures, letters, and words that can attract interest in learning for early childhood. This study aims to see the effect of the effectiveness of flashcard media on the ability to read the beginning and think symbolically in early childhood 5-6 at Imam Syafi'i Kindergarten. This study uses a simple regression analysis method to see the effect of effectiveness of flashcard media on the ability to read beginning and think symbolically in early childhood 5-6 in Imam Syafi'i Kindergarten. It was concluded that partially the flash card media had a significant effect on beginning reading ability, partially the flash card media had a significant effect on children's symbolic thinking while simultaneously the flash card media had a significant effect on children's beginning reading ability and symbolic thinking